Different carbon sources affect PCB accumulation by marine bivalves - Laitano, Marìa Victoria (2016)
Pampean creeks were evaluated in the present study as potential land-based sources of PCB marine contamination. Different carbon and nitrogen sources from such creeks were analysed as boosters of PCB bioaccumulation by the filter feeder bivalve Brachidontes rodriguezii and grazer limpet Siphonaria lessoni. Carbon of different source than marine and anthropogenic nitrogen assimilated by organisms were estimated through their C and N isotopic composition. PCB concentration in surface sediments and mollusc samples ranged from 2.68 to 6.46 ng g-1 (wet weight) and from 1074 to 4583 ng g-1 lipid, respectively, reflecting a punctual source of PCB contamination related to a landfill area. Thus, despite the low flow of creeks, they should not be underestimated as contamination vectors to the marine environment. On the other hand, mussels PCB bioaccumulation was related with the carbon source uptake which highlights the importance to consider this factor when studying PCB distribution in organisms of coastal systems.